The Influence of Female Clergy in Anglican Church of Uganda: With Specific Reference to the Diocese of Kigezi, All Saints Archdeaconry - Frank Bindeba Akatuhurira (Uganda Christian University, 2025)
The study examined the influence of female clergy in Anglican Church of Uganda with specific reference to the Diocese of Kigezi, All Saints Archdeaconry. It looked at the contributions, challenges and possible solutions to the challenges faced by female clergy in performing their tasks and assignments in the Anglican church of Uganda in the Diocese of Kigezi and especially in All Saints Archdeaconry. The study used cross sectional research design. The qualitative method in data analysis, questionnaires and Interview guides as instruments in data collection were used. The sample size had 31 respondents including 7 female clergy, 6 male clergy and 18 lay Anglican Christians. The study found out that female clergy have significant duties that they play in the growth of the Anglican Church. These roles included: spreading Christianity, being role models, educators and uniting people, the challenges faced included family issues like raising up children, caring for husbands, there was also disunity and lack of time to fully do their work. The solutions to the challenges included having debates, seminars and emphasising education for all. The study concluded that; female clergy promote church growth through spreading Christianity, being role models to other women, fostering unity and cooperation in the church of Uganda especially in the Diocese of Kigezi.
Undergraduate Research